Contribution to the Optimization of the Smelting Reduction of Nickeliferous Laterites, Based on the Recent Industrial Experience - Charalabos Zografidis; Konstantinos Betsis (Materials Proceedings, 2023)
The Greek ferronickel industry faces the challenge of restructuring and reoperation in the future, given that privatization is in progress, including the acquisition of the company’s assets for a joint venture enterprise. Within this framework, the current paper aims to contribute to the discussion about developing a new management strategy for the optimization of the pyrometallurgical process, focusing on the critical step of smelting reduction. Based mainly on industrial experience, factors which critically affect the safety and cost-effectiveness of smelting reduction are detected and presented, also by means of case studies, being classified as follows: (i) optimal raw materials’ feed management, including laterite ores (domestic or not), solid fuels and electrode paste; (ii) focus on preventive maintenance management. Substantial increase in the facilities’ operational index and cost saving is obtained; (iii) modern human resources management strategy, enhancing evaluation indicators’ use, education culture, process standardization and tacit—explicit knowledge management. Their economic footprint is discussed.